1997
DOI: 10.1093/ajcn/65.3.803
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of postmenopausal women to supplemental dietary boron and aluminum during usual and low magnesium intake: boron, calcium, and magnesium absorption and retention and blood mineral concentrations

Abstract: Findings from animal studies indicate that dietary boron affects several aspects of mineral metabolism, especially when animals are subjected to nutritional stressors. Eleven postmenopausal volunteers living on a metabolic ward for 167 d (one 23-d equilibration period and six 24-d treatment periods) were fed a conventional basal diet that supplied a daily average intake of 0.36 mg B, 109 mg Mg, and < 0.10 mg A1/8400 kJ. They were given supplements of 0 (BB) or 3 mg B (SB, last two periods only), 0 (BMg) or 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 25 publications
1
51
1
Order By: Relevance
“…Whereas, at the molecular level, Boron influences the activities of at least 26 enzymes (Hunt, 1998) and many of these enzymes are essential in energy substrate metabolism. In addition, it has been shown that Boron has many regulative roles in macromineral metabolism (Brown et al, 1989;Hegsted et al, 1991), energy metabolism (Hunt et al, 1997) and on the immune system (Hunt and Idso, 1999). Data of fructose concentration in seminal plasma (Table 1) revealed that there was a significant decrease in fructose concentration (p#0.05) after feeding bucks on different levels of boric acid compared to the control group.…”
Section: Results and Discussion Semen Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, at the molecular level, Boron influences the activities of at least 26 enzymes (Hunt, 1998) and many of these enzymes are essential in energy substrate metabolism. In addition, it has been shown that Boron has many regulative roles in macromineral metabolism (Brown et al, 1989;Hegsted et al, 1991), energy metabolism (Hunt et al, 1997) and on the immune system (Hunt and Idso, 1999). Data of fructose concentration in seminal plasma (Table 1) revealed that there was a significant decrease in fructose concentration (p#0.05) after feeding bucks on different levels of boric acid compared to the control group.…”
Section: Results and Discussion Semen Characteristicsmentioning
confidence: 99%
“…The increase thyroid gland activity and its thyroxin hormone secretion in the Boron groups may be due to the effect of Boron on stimulate energy metabolism. According to Hunt et al (1997), Boron has many regulative roles in energy metabolism (Hunt et al, 1997), moreover, Boron influenced the activities of at least 26 enzymes (Hunt, 1998) and many of these enzymes are essential in energy substrate metabolism. Treating male rabbits with 100, 200 and 400 mg boric acid/kg feed boosted blood testosterone concentration to reach 23.6, 24.4 and 29.5%, respectively above the untreated group values which was not significant.…”
Section: Blood Biochemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It interacts with calcium, vitamin D, and magnesium, which are all important in bone metabolism. Boron also increases steroid hormone concentrations in postmenopausal women and has antioxidant properties, which could make it beneficial in preventing atherosclerosis (Hunt et al, 1997;Hunt, 1998;Devirian and Volpe, 2003). Recently, the Expert Committee on Trace Elements in Human Nutrition of the World Health Organization concluded that boron is probably essential in human nutrition (WHO, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It increases steroid hormone concentrations and has antioxidant properties in postmenopausal women 9,11 . There is also evidence that B plays a role in healthy bones and joints 12,13 .…”
mentioning
confidence: 99%